Maslow's hierarchy of needs theory in environmental sociology: systematic literature review on the use of a theory - Abu Hurairah Abu Bakar; Mohamad Fauzi Sukimi; Mimi Hanida Abdul Mutalib (Penerbit Universiti Kebangsaan Malaysia, 2025)
As part of humanities study, environmental sociology research should be based on humanities theories. Various theories have been used in environmental sociology research, including Maslow's Hierarchy of Needs (HON) theory. A literature review is needed to determine the popularity and application of HON. From the online databases Scopus and Web of Science, 26 relevant and eligible research articles were found to be studied. Although HON was found in environmental sociology articles published in 2005, the increase has only been seen since 2020. This article contains a table describing how HON has been used in the 26 articles found. In conclusion, the environmental sociology research articles that mostly use HON were published in 2023 and were written by researchers from China. The 26 articles can be grouped into several fields of study, including environmental behaviour, urban development, community adaptation, green technology, resource management, and eco-friendly transportation. Most studies still rely on secondary data source and use statistical analysis.